1991
DOI: 10.1007/bf01986578
|View full text |Cite
|
Sign up to set email alerts
|

Effect of etodolac, a new nonsteroidal anti-inflammatory drug, in MRL/lpr mice with articular lesions

Abstract: Etodolac, a new nonsteroidal anti-inflammatory drug, was administered orally at doses of 1 and 5 mg/kg to MRL/MpJ-lpr/lpr (MRL/lpr) mice, and its effect on articular lesions was compared with that of indomethacin. Both etodolac and indomethacin significantly reduced swelling of the hind paw. Histopathological examination showed that etodolac significantly reduced cartilage and bone damage, whereas indomethacin treatment did not achieve a statistically significant effect. Rheumatoid factors were not affected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The treatment with ER-34122 did not suppress serum RF levels nor enlargement of lymph nodes as shown in Table 2 and 3. Indomethacin also did not affect on RF levels or lymph nodes weight as reported previously [9,11].…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…The treatment with ER-34122 did not suppress serum RF levels nor enlargement of lymph nodes as shown in Table 2 and 3. Indomethacin also did not affect on RF levels or lymph nodes weight as reported previously [9,11].…”
Section: Discussionsupporting
confidence: 64%
“…Carlson et al reported that the severity and incidence of the arthritis was not affected by treatment with aspirin at the dose of 100 mg/kg/day [8], and Rordorf et al also reported indomethacin (0.5 and 1 mg/ kg/day) and piroxicam (0.5 mg/kg/day) were inactive in the arthritis [9,10]. It was also shown that indomethacin (1 mg/kg/day) could not suppressed indexes of synovial and subsynovial lesion [11]. Therefore, our results showing lack of suppressive effect of indomethacin (1 mg/kg/day) on indexes of late articular lesion are consistent with previous reports.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…30 It was reported that COX-2 inhibitor, Nsaids, delayed the development of arthritis and reduced cartilage and bone damage using the MRL/lpr mice. 36 Therefore, the inhibition of Cox-2 may play an important role in the suppression of inflammation. In our study, the histopathological scores indicated that the inflammatory responses during synovitis may be inhibited by LIPUS treatment.…”
Section: Discussionmentioning
confidence: 99%
“…36 Tissue samples were dissected from knee joints after LIPUS treatment and examined by histopathological observation. Right knee joints (Fig.…”
Section: Antiarthritic Effect Of Lipus On the Mrl/lpr Micementioning
confidence: 99%